Proceedings of the International Conference on Tourism, Economics, Accounting, Management, and Social Science (TEAMS 2018) 2019
DOI: 10.2991/teams-18.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital Disclosure and Firm Value: Does Jokowi’s Era Matter?

Abstract: The purpose of this study is to observe the impact of Intellectual Capital Disclosure (Human Capital Disclosure, Structural Capital Disclosure, and Relational Capital Disclosure), Firm Size and Leverage towards the firm value (measured by Tobin's Q). This study examines 36 Indonesia's listed companies from infrastructure, utility, and transportation industry in 5 years period, from 2013 to 2017. The periods that have been chosen in order to differentiate the performance of 2 years before and 3 years of Joko Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…(Ardianto & Rivandi, 2018), (Subaida, Nurkholis, & Mardiati, 2018). (Primary, Sasongko, & Innayah, 2020), (Hatane, Angeline, Wedysiage, & Saputra, 2019) Firm value is defined as the price that potential investors can pay if a company is to be sold. The better the value of the company will increase the welfare of the owner of the company.…”
Section: The Value Of the Companymentioning
confidence: 99%
“…(Ardianto & Rivandi, 2018), (Subaida, Nurkholis, & Mardiati, 2018). (Primary, Sasongko, & Innayah, 2020), (Hatane, Angeline, Wedysiage, & Saputra, 2019) Firm value is defined as the price that potential investors can pay if a company is to be sold. The better the value of the company will increase the welfare of the owner of the company.…”
Section: The Value Of the Companymentioning
confidence: 99%
“…Thirdly, the conclusions about the influence of intellectual capital on the value of enterprises also cause many concerns for policy makers, economic managers, enterprises and related objects. There are a lot of studies showing the positive impact between knowledge and business performance such as Chen et al (2005), Clarke et al (2011), Sayad and Pourmohammadi (2014), Ozkan et al (2017) but also some studies show the opposite effect as the topic of Girma (2017) or points out that there is no relationship between IC and performance (Firer and Williams, 2003), (Hatane et al, 2019). The inconsistency in research results is due to specific characteristics of the sample, study time and specific characteristics of each economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research by [12] found different results. Intellectual capital disclosure has a significant negative effect on firm value.…”
Section: Introductionmentioning
confidence: 94%